2015
DOI: 10.5301/jabfm.5000219
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Protein Adsorption onto Alumina Nanoparticles Relevant to Orthopedic Wear

Abstract: Proteins associated with opsonization of particles were seen to be present in the protein corona of the nanoparticles, which raises questions regarding the role of wear particles in periprosthetic tissue inflammation and aseptic loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Some studies have proposed that the wear property of bioceramics consequences in releasing nanoparticles in vivo which provide a dissimilar biological behavior from their origin formation. Gibbons and his team (Gibbons et al, ) have recently studied the adsorption of human plasma proteins on alumina nanoparticles and monolithic substrates which were the illustrative of both wear particles and bioceramic constituents. The results presented an obvious dissimilarity between the adsorb proteins on nanosurfaces in comparison with macrosurfaces, which some studies have explained some potential reasons for it (Lynch & Dawson, , ).…”
Section: Protein Adsorption and Cell Responses To Alumina Surface Pro...mentioning
confidence: 99%
“…Some studies have proposed that the wear property of bioceramics consequences in releasing nanoparticles in vivo which provide a dissimilar biological behavior from their origin formation. Gibbons and his team (Gibbons et al, ) have recently studied the adsorption of human plasma proteins on alumina nanoparticles and monolithic substrates which were the illustrative of both wear particles and bioceramic constituents. The results presented an obvious dissimilarity between the adsorb proteins on nanosurfaces in comparison with macrosurfaces, which some studies have explained some potential reasons for it (Lynch & Dawson, , ).…”
Section: Protein Adsorption and Cell Responses To Alumina Surface Pro...mentioning
confidence: 99%
“…e result showed that the nanoparticles are highly stable up to 24 h and are less toxic towards Chinese Hamster Ovary (CHO) cells [247]. e reduced toxicity may be due to the enhanced protein adsorption ability [241], especially human plasma proteins [248]. Moreover, Rajiv et al [249] evaluated the cytotoxicity and genotoxicity of cobalt, iron, silicon, and aluminum oxide nanoparticles towards human lymphocyte cell lines.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Gulsen, Merve, and Meltem et al, worked on bio tribology of ligament wear in the knee and hip joints survey of present improvements. [10][11][12][13][14][15][16][17][18][19][20][21] This review article aimed to provide an overview of in-vitro studies at the theoretical and laboratory conditions that must be performed before clinical investigation. In the experiment, utilizing the essential standards of tribology and utilizing new techniques that would be utilized in the field of bio-tribology are investigated.…”
Section: Recent Research Of Tribology In Biomedical Engineeringmentioning
confidence: 99%